Study on the Construction Plan of Countryside Type Ecological Belt Based on Ecological Orientation:Taking the Ecological Restoration of Ecological Belt of Chunzi River in Longgang District,Shenzhen as an Example - TANG Yawen; LIU Xuepeng; HUANG Yilong; YU Yuanyan; LUO yao (Renmin Zhujiang)
Ecological belt,is the innovative practice of ecological civilization in Guangdong province,the idea and interpretation of happy rivers and lakes,and the product of water management to a certain stage.In order to explore the methods and approaches of ecological restoration in the construction of ecological belt,taking the ecological belt of Chunzi River in Longgang District,Shenzhen as an example,this paper investigates and monitors the water environment and water ecology of Chunzi River in detail by means of field investigation and experimental analysis,and proposes systematically the water ecological restoration scheme in ecological belt construction according to the theory of focal species.The results indicate that:①Through analyzing the structure and diversity indices of aquatic organisms,the water bodies are in a moderate to heavy pollution state,and higher aquatic organisms are dominated by exotic fishes.The aquatic ecosystem is severely damaged;while the terrestrial ecosystem is less disturbed.②The sewage treatment plant (with effluent water quality reaching the ready class III) — integrated constructed wetland-reservoir water quality purification system,the habitat improvement system of optimized forest structure in mountain-waterfront-shallow,and the symbiotic stable ecosystem of “submerged plants-floating-leaved plants-emergent plants-zooplankton-fish” are put forward,and a water ecology pattern of conservation-recreation-protection is built.③In the future,combined with the implementation of the project,continuous monitoring of water environment and water ecology will be carried out,and restoration scheme will be optimized and improved,so as to provide Shenzhen sample for the construction of ecological belt in Guangdong Province.